THE INFLUENCE OF POTASSIUM DICHROMATE Cr (VI) ADMINISTRATION DURATION ON GLOBULAR RESISTANCE IN FEMALE RATS - LETIŢIA STANA; ALEXANDRA TRIF; SNEJANA PETROVICI; LOREDANA GABRIELA STANA; CORINA GRĂVILĂ (Scientific Papers Animal Science and Biotechnologies, 2023)
The „in vivo” experiment has had as aim the study of different Cr(VI) doses administration on globular resistance in female rats related to administration duration. Study was carried out on 56 female rats divided in 8 groups, 6 experimental and 2 control that received potassium dichromate in drinking water in doses of 25 ppm, 50 ppm and 75ppm Cr(VI), for 3 months, respectively, 6 months. Decrease of globular resistance (in terms of haemolysis degree in hypotonic solutions) at increasing dose (up to 0.8% NaCl at 75 ppm dose) in all experimental groups, in direct relation with the duration of administration was registered. Control groups were in physiological limits. The results of the present study revealed the affecting of erythrocyte membrane in function of administration duration and chromium intake level, because of oxidative lesions produced by it.